The Role of Christian Family Education in Anticipating Sexual Deviations in Society - Marbun, Nurmiati; Imeldawati, Tiur; Sihombing, Enja; Lukita Dewi, Elisabeth Savitri; Br Torus, Melda Depita (LPPM IAKN Tarutung, 2023)
The purpose of this research was to provide an explanation of the first things to discover and explain the issue of sexual deviation as part of a Bible study. Second, to find and explain the factors that cause sexual deviation in society even though Allah only created men and women. This research is motivated by the author's concern with a phenomenon that exists in society, namely LGBT issues as something that is trending. Using qualitative methods in the form of interviews and literature studies, it was found that the family is the main person responsible for anticipating deviant sexual behavior in children. Parents are role models in spirituality who must instill the fear of God in their children, so that children find the correct self-image as God's creation, namely boys and girls. Families also need to provide proper education and encourage children to become future generations who make achievements and are proud of being children. The Bible must be the basic reference for spiritual education in the family. Keywords: family education, sexual deviation.